Structuring and Restructuring Sovereign Debt: The Role of Seniority1 - BOLTON, PATRICK; JEANNE, OLIVIER (Review of Economic Studies, 2009)
We show how the willingness-to-pay problem and lack of exclusivity in sovereign lending may result in an equilibrium sovereign debt structure that is excessively difficult to restructure. A bankruptcy regime for sovereigns can alleviate this inefficiency but only if it is endowed with far-reaching powers to enforce seniority and subordination clauses in debt contracts. A bankruptcy regime that makes sovereign debt easier to restructure without enforcing seniority may decrease welfare. Copyright Copyright © 2009 The Review of Economic Studies Limited.